Let's Start Talking: University Accelerators and Their Strategic Intent Alignment with Entrepreneurship Education in Indonesia. - Maritz, Alex; Arisian, Sobhan; Ardyan, Elia; Ongkowijoyo, Gracia (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
This paper aims to explore the significance of university accelerators (UAs) in Indonesia by examining neoteric global best practices for aligning university entrepreneurship strategic intent. We introduce an iterative aspect and emerging investigation into multi-method research, which includes a quantitative examination of Indonesian UAs and analyses of entrepreneurial strategic objectives and narratives based on best practice accelerator applications. Our findings demonstrate the scarce allocation of UAs in Indonesia and the lack of alignment with the strategic intent of universities. Additionally, we found no evidence of entrepreneurship education (EE) integration in Indonesia, indicating the successful outcomes mostly present from the self-effort of students' nascent startups rather than educational impacts. Collaborative and engagement aspects of UAs in broader entrepreneurial ecosystems may deliver a better platform for societal upliftment within an Indonesian context.